New host and distribution expansion for Pterygodermatites (Multipectines) affinis - Scioscia N. P.; Beldomenico P. M.; Denegri G. M. (Helminthologia, 2016)
The present study reports the first case of infection by Pterygodermatites affinis in Lycalopex gymnocercus, and the first report of this nematode in Argentina. Examining 80 foxes from Buenos Aires province, specimens of this species were recovered from 21.25 % of the small intestines and eggs were found in 7.5 % of the fecal samples.